2014
DOI: 10.1002/nbm.3184
|View full text |Cite
|
Sign up to set email alerts
|

Amide proton transfer‐weighted imaging of the head and neck at 3 T: a feasibility study on healthy human subjects and patients with head and neck cancer

Abstract: The aim of this study was to explore the feasibility and repeatability of amide proton transfer weighted (APTw) MRI for the head and neck on clinical MRI scanners. Six healthy volunteers and four patients with head and neck tumors underwent APTw-MRI scanning at 3T. The APTw signal was quantified by the asymmetric magnetization transfer ratio (MTRasym) at 3.5 ppm. Z-spectra of normal tissues in the head and neck (masseter muscle, parotid glands, submandibular glands and thyroid glands) were analyzed in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 55 publications
3
62
1
Order By: Relevance
“…The actual water resonance was assumed to be at the frequency associated with the lowest intensity of the fitted Z-spectrum. Then, the interpolated Z-spectrum was shifted to the 0 ppm of the offset axis to correct for the field heterogeneity ΔB 0 [11]. The magnitude of the CEST effect was quantified as a magnetization transfer asymmetry ratio (MTR asym ): MTRasym0.2emfalse(normalΔnormalΩfalse)=Sfalse(normalΔnormalΩfalse)S0Sfalse(normalΔnormalΩfalse)S0where ΔΩ denotes the shift difference between irradiation frequency and the water resonance, and S and S 0 are the saturated and nonsaturated image intensities, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The actual water resonance was assumed to be at the frequency associated with the lowest intensity of the fitted Z-spectrum. Then, the interpolated Z-spectrum was shifted to the 0 ppm of the offset axis to correct for the field heterogeneity ΔB 0 [11]. The magnitude of the CEST effect was quantified as a magnetization transfer asymmetry ratio (MTR asym ): MTRasym0.2emfalse(normalΔnormalΩfalse)=Sfalse(normalΔnormalΩfalse)S0Sfalse(normalΔnormalΩfalse)S0where ΔΩ denotes the shift difference between irradiation frequency and the water resonance, and S and S 0 are the saturated and nonsaturated image intensities, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For these protein ST effects, several interesting correlations have been shown that might play a role in vivo and especially in pathologies: dependence on intracellular pH (5,(10)(11)(12)(13), protein concentration (8,13), or protein folding (14,15) and aggregation states (16). Already, the use for brain tumor detection (6,(17)(18)(19)(20), grading (21), and possible differentiation of tumor recurrence and radiation necrosis (22) has been shown to be feasible by proteinbased saturation transfer MRI.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of using APT imaging is that the MRI contrast at the cellular protein level is achieved indirectly through the bulk water signal used in daily imaging. Many encouraging results have been reported by different research groups, regarding promising APT-weighted (APTW) signals as image biomarkers for brain tumours [2227] and other cancers in the prostate, breast, and neck [2831], and for cerebral ischemia [3234], Parkinson’s disease [35], and ventral hernia [36]. To the best of our knowledge, PCNSLs have never been studied with APT imaging, and the APT-MRI parameters have also not been quantitatively compared between PCNSLs and HGGs.…”
Section: Introductionmentioning
confidence: 99%